2009
DOI: 10.1080/09669760902982331
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphically speaking: on communication between teachers and children in early childhood biology education

Abstract: Title:Teacher talk and children's queries: Communication about natural science in early childhood education Language: Swedish with a summary in English

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
0
39
0
7
Order By: Relevance
“…This is problematic while a wrong science understanding (for example instead of a biological explanation about growth of plants, photosynthesis, children think plants absorb nutrition from the earth), remains during school-life (Driver et al1985). Based on Ejby-Ernst (2012), Thulin (2011) and Thulin and Pramling (2009) Danish and Swedish nature science education in preschool contributes to a limited and also wrong science thinking. Children's science understanding is characterized by an anthropocentric thinking, they think the world is created by humans and human beings are center of the world.…”
Section: The Appearance Of Science Education In Preschoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic while a wrong science understanding (for example instead of a biological explanation about growth of plants, photosynthesis, children think plants absorb nutrition from the earth), remains during school-life (Driver et al1985). Based on Ejby-Ernst (2012), Thulin (2011) and Thulin and Pramling (2009) Danish and Swedish nature science education in preschool contributes to a limited and also wrong science thinking. Children's science understanding is characterized by an anthropocentric thinking, they think the world is created by humans and human beings are center of the world.…”
Section: The Appearance Of Science Education In Preschoolsmentioning
confidence: 99%
“…That is when the child'smotive corresponds with the purpose of the activity (Leontjev, 1978). Taking cildren's existing knowledge as starting point is a robust principle (Ausubel and Robinson, 1971), however while children's own construction of explanation often are inadequate, for instance characterized by an 'anthropomorphical understanding (Thulin and Pramling, 2009) at the same time the preschool teacher has to challenge, discuss and put the child's thoughts in perspective. Opposite as earlier mentioned such an understanding can be stabilized and last over years (Driver, 1981;Driver, Guesne, and Tiberghien, 1985).…”
Section: Child's Perspective Wonder Inquisitiveness and Experiencesmentioning
confidence: 99%
“…Previous LS projects (e.g., Ljung-Djärf et al, 2014) as well as other projects (e.g., Thulin, 2011;Thulin & Pramling, 2009) have questioned the combination of play and anthropomorphic speech and learning, suggesting that play or a playful approach can even obscure the object of learning. In contrast, the presented LS displayed a good ability to combine a playful framing with a variation theory perspective in order to stimulate children's understanding of why shadows occur.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…In contrast, other research into playful science learning has demonstrated that the use of play and imagination can limit or even obscure the intended science content. Thulin and Pramling (2009), for example, have found that figurative language that humanizes animals and inanimate objects is a common strategy for connecting children's experiences and terms, on one hand, with children's developing understanding, on the other. Such anthropomorphic speech is also used to give the science content a playful inviting frame.…”
Section: Young Children Learning About Sciencementioning
confidence: 99%
“…Ett exempel på detta utgörs av en studie som rör kommunikation om naturvetenskapliga fenomen. Resultaten visade att en hög andel antropomorfistiskt (att tala om djur i mänskliga termer) tal förekom och att det främst var lärarna som använde detta språkbruk (Thulin & Pramling, 2009). Resultaten visar också att vid ett ensidigt användande -om än i vällovligt syfte -av antropomorfistiskt tal riskerar kommunikationen att stanna på en vardaglig nivå och tenderar att skymma det naturvetenskapliga innehållet.…”
Section: Förskolan Som En Miljö För Lärande Av Ett Innehållunclassified